ANALISIS MATEMATIKA PERBANDINGAN METODE DIVIDE & BROADCAST DAN METODE DIVIDE & PARTIAL BROADCAST - adam, Pasrun; Cahyono, Edi (MATEMATIKA, 2010)
In this article we discuss the comparison of Divide & Broadcast Method (DBM) and Divide & Partial Broadcast Method. Both are data processing methods. From mathematical point of view the methods are to seek a relation of two sets of a large amount of data, too large for one processor. The comparison is based on three basic computations of the matching of two sets i.e. multiplication, addition and logarithm. The comparison is to obtain the efficiency of the methods. Previous researches have shown that based on multiplication and addition DPBM is more efficient than DBM, but the result based on logarithm is still unknown. In this article we report our result on the comparison of DBM and DPBM based on logarithm computation. Â